Exploring the In Vivo Role of the Mitochondrial Calcium Uniporter in Brown Fat Bioenergetics - Daniel Flicker; Yasemin Sancak; Eran Mick; Olga Goldberger; Vamsi K. Mootha (Cell Reports, 2019)
Summary: The mitochondrial calcium uniporter has been proposed to coordinate the organelle’s energetics with calcium signaling. Uniporter current has previously been reported to be extremely high in brown adipose tissue (BAT), yet it remains unknown how the uniporter contributes to BAT physiology. Here, we report the generation and characterization of a mouse model lacking Mcu, the pore forming subunit of the uniporter, specifically in BAT (BAT-Mcu-KO). BAT-Mcu-KO mice lack uniporter-based calcium uptake in BAT mitochondria but exhibit unaffected cold tolerance, diet-induced obesity, and transcriptional response to cold in BAT. Unexpectedly, we found in wild-type animals that cold powerfully activates the ATF4-dependent integrated stress response (ISR) in BAT and upregulates circulating FGF21 and GDF15, raising the hypothesis that the ISR partly underlies the pleiotropic effects of BAT on systemic metabolism. Our study demonstrates that the uniporter is largely dispensable for BAT thermogenesis and demonstrates activation of the ISR in BAT in response to cold. : Flicker et al. generate a mouse lacking mitochondrial calcium uniporter activity in brown fat. They show that the uniporter is dispensable for brown fat bioenergetics. Unexpectedly, they find that in wild type animals, cold stress induces ATF4 signaling in normal brown fat, suggesting a mechanism for cold-induced GDF15 and FGF21 elevation. Keywords: mitochondria, calcium, uniporter, MCU, brown fat, thermogenesis, ATF4, integrated stress response, FGF21, GDF15